Analysis of Financial Services Authority (OJK) Regulation No. 12 of 2023 on Sharia Business Units in Mitigating the Impact of Inflation on Sharia Banking in Bengkulu Province - Icha Puspita; Idwal B; Yetti Afrida Indra (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Inflation in Bengkulu Province has weakened public purchasing power and the real sector, while simultaneously elevating Non-Performing Financing (NPF) risks and destabilizing Third-Party Funds (DPK) in Islamic banking. In response, the Financial Services Authority (OJK) issued POJK No. 12/2023 on Sharia Business Units (UUS). This regulation aims to fortify institutional frameworks, capital, governance, and Sharia compliance, enabling UUS to better withstand inflationary shocks. This study examines the regulation's core provisions, its implementation in Bengkulu, and its impact on regional banking stability. Method: This descriptive qualitative study employs a library research approach, analyzing secondary data from official OJK, Bank Indonesia, and BPS reports on regional economics, inflation, and banking performance. Data were collected via documentary study and analyzed using content and qualitative descriptive analysis, involving data reduction, narrative presentation, and conclusion drawing. Results: The findings reveal that POJK 12/2023 reinforces UUS resilience through mandatory minimum core capital, spin-off requirements into full Sharia Commercial Banks, strengthened Sharia Supervisory Boards, and stricter governance audits. In Bengkulu, these measures are supported by OJK Regional Office VI supervision, outreach via TPID and TPAKD forums, and local adjustments in capital and risk management. Conclusion: Overall, POJK 12/2023 is positively contributing to Islamic banking stability in Bengkulu. However, its full potential is constrained by persistently low Islamic financial literacy and limited banking accessibility in rural areas, which continue to hinder broader economic impact.